Differences in trunk kinematic between frail and nonfrail elderly persons during turn transition based on a smartphone inertial sensor - Galán-Mercant, Alejandro; Cuesta-Vargas, Antonio (Wiley, 2013)
Objective: Firstly, to, through instrumentation with the iPhone4 smartphone, measure and describe variability of tridimensional acceleration, angular velocity, and displacement of the trunk in the turn transition during the ten-meter Extended Timed-Get-up-and-Go test in two groups of frail and physically active elderly persons. Secondly, to analyse the differences and performance of the variance between the study groups during turn transition (frail and healthy). Design: This is a cross-sectional study of 30 subjects over 65 years, 14 frail subjects, and 16 healthy subjects. Results: Significant differences were found between the groups of elderly persons in the accelerometry (P < 0.01) and angular displacement variables (P < 0.05), obtained in the kinematic readings of the trunk during the turning transitions. The results obtained in this study show a series of deficits in the frail elderly population group. Conclusions: The inertial sensor found in the iPhone4 is able to study and analyse the kinematics of the turning transitions in frail and physically active elderly persons. The accelerometry values for the frail elderly are lower than the physically active elderly, whilst variability in the readings for the frail elderly is also lower than the control group.
Keywords: Informática médica; Smartphone; Elderly persons; Kinematics; Trunk